Evaluation of prevalance and risk factors for bloodstream infection in severe coronavirus disease 2019 (COVID-19) patients. Issue 1 (21st February 2022) - Erbay, Kubra; Ozger, Hasan Selcuk; Guzel Tunccan, Ozlem; Gaygısız, Ümmügülsüm; Buyukkoruk, Merve; Sultanova, Fidan; Yıldız, Mehmet; Boyacı Dündar, Nazlıhan; Aydoğdu, Müge; Bozdayi, Gulendam; Dizbay, Murat
Abstract: Objectives: In this study, we sought to determine the prevalence of bloodstream infection (BSI) in severe coronavirus disease 2019 (COVID-19) patients and to determine the risk factors of BSI in critical COVID-19 patients. Design: Retrospective, descriptive study between March 2020 and January 2021. Setting: An 1, 007-bed university hospital. Participants: Patients who were hospitalized due to severe COVID-19 disease and had an aerobic blood culture taken at least once during hospitalization Methods: Case definitions were made according to National Institutes of Health clinical definitions. According to the blood culture results, the patients were grouped as with and without BSIs, and compared for BSIs risk factors. Results: In total, 195 patients were included in the study. Blood culture positivity was detected in 76 (39.0%) of 196 patients. Excluding blood culture positivity considered as contamination, the prevalence of BSI in all severe COVID-19 cases was 18.5% (n = 36). In intensive care unit patients the prevalence of BSI was 30.6% (n = 26). In multivariate analyses, central venous catheter (odds ratio [OR], 8.17; 95% confidence interval [CI], 2.46–27.1; P < .01) and hospitalization in the multibed intensive care unit (OR, 4.28; 95% CI, 1.28–14.3; P < .01) were risk factors associated with the acquisition of BSI. Conclusion: The prevalence of BSI in COVID-19 patients is particularly high in critically ill patients. The central venous catheter and multibed intensive care follow-up are risk factors for BSI. BSIs can be reduced by increasing compliance to infection control measures and central venous catheter insertion-care procedures. The use of single-bed intensive care units where compliance can be achieved more effectively is important for the prevention of BSIs.